MicroRNAs in Transforming Growth Factor-Beta Signaling Pathway Associated With Fibrosis Involving Different Systems of the Human Body - Xu, Xiaoyang; Hong, Pengyu; Wang, Zhefu; Tang, Zhangui; Li, Kun (Frontiers in Molecular Biosciences, 2021)
Fibrosis, a major cause of morbidity and mortality, is a histopathological manifestation of many chronic inflammatory diseases affecting different systems of the human body. Two types of transforming growth factor beta (TGF-β) signaling pathways regulate fibrosis: the canonical TGF-β signaling pathway, represented by SMAD-2 and SMAD-3, and the noncanonical pathway, which functions without SMAD-2/3 participation and currently includes TGF-β/mitogen-activated protein kinases, TGF-β/SMAD-1/5, TGF-β/phosphatidylinositol-3-kinase/Akt, TGF-β/Janus kinase/signal transducer and activator of transcription protein-3, and TGF-β/rho-associated coiled-coil containing kinase signaling pathways. MicroRNA (miRNA), a type of non-coding single-stranded small RNA, comprises approximately 22 nucleotides encoded by endogenous genes, which can regulate physiological and pathological processes in fibrotic diseases, particularly affecting organs such as the liver, the kidney, the lungs, and the heart. The aim of this review is to introduce the characteristics of the canonical and non-canonical TGF-β signaling pathways and to classify miRNAs with regulatory effects on these two pathways based on the influenced organ. Further, we aim to summarize the limitations of the current research of the mechanisms of fibrosis, provide insights into possible future research directions, and propose therapeutic options for fibrosis.